USABILITY TESTING METHODS FOR ASSESSING A MOBILE APPLICATION - KRAVCHENKO, Svitlana; MARCHUK, Galina; LOKTIKOVA, Tamara; GRISHKUN, Yevgenii (Herald of Khmelnytskyi National University. Technical sciences, 2023)
When conducting research to study the usability of a web page, user interface or device for its further mass use, usability testing is used. The usability test helps to find the best solution of the interface from all efforts, as well as to check the suitability of the resource for users from different countries, when, for example, language switching is provided. The work analyzes various methods of usability testing for the ease of use of websites, applications and other interfaces. The main stages of UX testing and the scenario for interviewing respondents are defined.This article presents methods and evaluations of software product quality indicators testing. The object of the study is usability testing, as interaction with the software product, its perception by the target audience and quality assessment and determination of criteria for evaluating the usability of the mobile application for iOS for purchasing an electronic ticket for tourist trips. As a result of UX-testing, the weak points of the interface are revealed, which cause difficulties for users and the inconsistency of the interface with their expectations. Based on the results of testing, the developers refine the product and bring it to the optimal user requirements.Usability testing was conducted using a survey of respondents without the participation of a moderator. A scheme for step-by-step implementation of testing has been developed. Using a Likert scale, the application was evaluated using a questionnaire that includes five factors: learnability, efficiency, recall, errors, and satisfaction. The result for each criterion and the overall usability indicator of the model application were presented.
Keywords: Usability testing; User Experience; UI; application; methods; scenario; tasks; criteria